An Application of the Simple Additive Weighting Method in Recommendations for Contraception Tools (Case Study of BKKBN) - Orlando Bona Ganda; Jusuf Wahyudi; Aji Sudarsono (Jurnal Komputer, Informasi dan Teknologi, 2021)
This study aims to create an application that can help provide recommendations for contraceptives that can be used based on the selected criteria and to apply the Simple Additive Weighting Method in the recommendation for contraceptives (BKKBN case study). This contraceptive recommendation application is made using the Visual Basic .Net programming language, where the application has implemented one of the Decision Support System Methods, namely Simple Additive Weighting. Contraceptives is a method used to prevent pregnancy. There are different types of contraception that can be used and each has its advantages and disadvantages. This application can help provide recommendations to users of contraceptives to choose a suitable tool for use with considerations, namely age, breastfeeding, number of children, blood pressure, body mass index. Based on the results of black box testing, the functionality of the application has been running properly and is able to display the results of contraceptive recommendations based on the SAW method process